Analisis Hubungan Antara Pengetahuan dan Sikap Terhadap Praktik Penggunaan Antibiotika oleh Peternak Babi di Kota Kupang Provinsi Nusa Tenggara Timur - Novalino Harold Geoffrey Kallau; I Wayan Teguh Wibawan; Denny Widaya Lukman; Mirnawati Baharudin Sudarwanto (Jurnal Sain Veteriner, 2018)
The prevalence of antibiotic resistance is an increasing problem due to the use of false and excessive antibiotics. The use of antibiotics in pig farms is increasing and needs to be aware of side effects, it is also influenced by the knowledge, attitudes and practices of farmers. This study is a cross-sectional study using a structured questionnaire interview to analyze the relationship between knowledge and attitudes towards the practice of using antibiotics by pig farmers in Kupang city. A total of 96 respondents pig farmers spread over 6 districts, District of Maulafa (9 villages) District of Alak (12 villages) District of Oebobo (7 villages), District of Kelapa Lima (5 villages), District of Kota Raja (2 villages) and the district of Kota Lama (1 village). The variables observed were individual characteristics, knowledge, attitudes and practices of the use of antibiotics by pig farmers in relation to the occurrence of antibiotic resistance. The relationship between the variables was tested using the Pearson correlation, while the relationship and magnitude of the direct and indirect impact on the observed variables was determined using path analysis. The results showed knowledge has a very significant impact (p <0.01) and indirectly contributes to the level of antibiotic usage practices preventing the occurrence of antibiotic resistance. Attitudes have a significant effect (p <0.05) and directly affect the practice of antibiotics to prevent the use of antibiotic resistance in Kupang. Conclusion of this study shows that knowledge has a major impact on the practice of using antibiotics by pig farmers, so by increasing farmers' knowledge of the facts incidence of antibiotic resistance, the attitude of farmers will increasingly have a positive significant effect on the level of practice use of antibiotics Prevent antibiotic resistance at a pig farm in the city of Kupang.